2012
DOI: 10.3350/cmh.2012.18.2.213
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features of drug-induced liver injury observed through liver biopsy: focus on relevancy to autoimmune hepatitis

Abstract: Background/AimsAccurate diagnosis of drug-induced liver injury (DILI) is difficult without considering the possibility of underlying diseases, especially autoimmune hepatitis (AIH). We investigated the clinical patterns in patients with a history of medication, liver-function abnormalities, and in whom liver biopsy was conducted, focusing on accompaniment by AIH.MethodsThe clinical, serologic, and histologic findings of 29 patients were compared and analyzed. The patients were aged 46.2±12.8 years (mean±SD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Ju et al [33] have studied the histological features of DILI patients in Korea, with special focus on relevancy of AIH. The study showed that characteristic histologic features of AIH, as interface hepatitis and lymphoplasmocytic infiltrates, were present in up to one third of DILI patients.…”
Section: Classificationmentioning
confidence: 99%
“…Ju et al [33] have studied the histological features of DILI patients in Korea, with special focus on relevancy of AIH. The study showed that characteristic histologic features of AIH, as interface hepatitis and lymphoplasmocytic infiltrates, were present in up to one third of DILI patients.…”
Section: Classificationmentioning
confidence: 99%
“…Viruses associated with the onset of AIH include: HAV, HCV, HEV, EBV, HSV and measles [3,24,27,28]. Drug-induced liver injury (DILI) can mimic, trigger or unmask AIH [29,30], and distinction between DILI and AIH can be challenging [30][31][32][33].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Since DILI can mimic, trigger or unmask AIH, distinction between DILI with features of AIH and true AIH requires scrutiny of clinical and histological differences [30][31][32][33]48,49].…”
Section: Differential Diagnostic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanism of DILI is still largely unidentified, it seems to involve 2 pathways -direct liver toxicity and adverse immune reactions (Holt and Ju, 2006). DILIs from herbal medicines are generally idiosyncratic drug reactions, strongly suggesting a mainly immune response (Ju et al, 2012). Immune responses against foreign antigens and malignant cells are lower in the elderly, and most immune cells involved in innate immunity show decreased function with aging (Tajiri and Shimizu, 2013).…”
Section: Tablementioning
confidence: 99%